Functional compounds in two accessions of Tropaeolum tuberosum during storage - Gómez Mamani, Roger (2021)
The functional compounds present in food are essential to prevent certain types of cancer, so it is important to know how they vary in the food during storage. The study was conducted in the Puno region in 2019; the objective of the trial was to evaluate the behavior of functional compounds in two accessions of Isaño: Yana añu (purple-dark color) and Yellow pumpkin with purple eyes during storage at natural conditions 13 ºC and 65 % of relative humidity. The method used to determine the polyphenols was the one described by Folin-Ciocalteu; ABTS to determine the CAOX and visual titration with 2-6 Dichlorophenolindophenol to quantify the vitamin C content. The results show that the Yana añu accession has the highest polyphenol content and antioxidant capacity compared to the yellow pumpkin with purple eyes accession, being these values for polyphenols 24.90 and 15.89 mg AGE.g-1, which are reduced to 15.93 and 4.89 mg AGE.g-1 respectively in both fresh state accessions. The same thing occurs for CAOX starting with 322.66 and 87.17 and reducing to 296.35 and 77.85 μmol TE.g-1 by day 40 of storage for both varieties. On the other hand, the Vitamin C content is similar in both cases, as indicated by Tukey's test. The loss of functional compounds in the two accessions of the Isaño is inversely related to the time of storage